Telecommunications Challenges in Developing Countries : Asymmetric Interconnection Charges for Rural Areas - Dymond, Andrew (Washington, DC: World Bank, 2013)
This report addresses the important issue of interconnection, the application and enforcement of which is widely recognized to be key to effective liberalization strategy, or often a key reason for failure. Nowhere is this more critical than in the area of rural telecommunications, where network costs are known to be high and where the traditional consensus has been that services cannot be rolled out without subsidies. In a liberalizing environment, the issue becomes even more critical. Rural areas must be better connected, but subsidies-even best-practice explicit subsidies applied in a so-called smart way-cannot cover all of the areas that will remain without service unless better means of incentivizing investment are explored. This report investigates an approach to rural telecommunications investment that would seek to bridge most of the so-called rural "access gap" by revising the network interconnection regime, such that operators serving high cost areas would receive higher call termination fees. The new regime would be built on geographically de-averaged termination charges, to be more indicative of network cost differences between urban and rural networks. The new system could change the business model for rural networks, harnessing the potential for incoming call revenues to shoulder much more of the investment feasibility than currently allowed. It is argued that the rural access gap could be bridged largely by more efficient pricing, thus reducing the need for subsidies, leaving only the most remote and challenging areas in need of financial support.